The Characteristics of Takeover Targets: Evidence from Food Industry in Serbia - Andrašić, Jelena; Mirović, Vera; Milenković, Nada; Pjanić, Milos; Kalaš, Branimir (Industrija, 2018)
This study analyses the characteristics of target companies from food industry that were taken over by foreign investors in the Serbian market. The aim of the study is to determine: Can future target companies be predicted based on the characteristics of target companies that have already been taken over in the Serbian market? The study compares the indicators of profitability, liquidity, leverage and efficiency of 30 target companies from the food industry with the industry' average. The study includes multivariate analysis of variance (Manova) and Discriminant analysis in order to identify the difference between observed indicators. The liquidity and leverage indicator showed a statistically significant difference compared to average values. Group classification is 95% and sample homogeneity is 90% which leads to a conclusion that target companies can be predicted with extremely high reliability.
Keywords: Takeover; Industries; Food industry